Bibliometric analysis of expatriates in the scope of human resource management (Asian Journal of Economics and Business Management, 2023)
In the current era of globalization in the workplace, employees no longer labor solely within a single nation. Current employees are also able to work abroad, apply for positions abroad, and work for domestic companies with overseas locations. This era of globalization affords us the chance to observe cross-cultural diversity and the development and expansion of intercultural interaction, so that expatriate adjustments are very significant and management of cross-cultural employees presents significant challenges. Expatriates are employees brought in by companies from abroad to be employed in the company. Expatriate employees are required to adapt to local culture and be able to manage their stress. This study uses Bibliometric Analysis as a research method using the keyword Expatriate. This study aims to find out the literature review related to expatriates in the scope of Human Resource Management. There were 7,193 articles found obtained from Scopus, then the articles were selected so that 123 articles were used in this study. This study also uses the Vos Viewer application to categorize and visualize co-authorship, co-accuracy, and citation.